Magnetic resonance spectroscopy imaging of medulla oblongata and substantia nigra in idiopathic Parkinson's disease - Rana, Netra; Ma, Shaohui; Guo, Chenguang; Li, Min; Zhang, Ming (Asian Journal of Medical Sciences, 2013)
Objective: To use 1.5T 1H-MRS as a research tool in vivo and demonstrate the feasibility of obtaining long-echo 1H MR spectra in small volumes like substantia nigra (SN) and medulla oblongata (MO) in healthy volunteers and patients with Parkinson's disease (PD) and observe the clinical correlations. Subjects and Methods: Twenty patients of the idiopathic Parkinson’s disease (IPD) were recruited from the Out Patient Department of Neurology. Additionally, 14 age-matched healthy subjects were taken as controls group. After baseline evaluation, the patients satisfying inclusion and exclusion criteria underwent 1H-MRS study. All MR examinations were performed on a 1.5 T system (Philips Gyroscan Intera, Netherlands) using a standard quadrature head coil. Results: We succeeded to achieve 74.19% and 77.42% of spectra from MO and SN of both PD and control groups. MO showed slightly weak negative result to total UPDRS and UPDRS- II, but no significant correlation was found between metabolites and clinical indexes in MO. The result also showed no significant correlations between H&Y scale and metabolites in MO and SN of PD patients. But there was a significant correlation between H&Y, NAA/Cr and Cho/Cr in SN. Conclusions: MRS ratios from MO and SN does not play any significant role to differentiate PD from the normal subjects, but metabolites ratios from SN of PD patient can help to understand the progression and severity of the disease. Therefore, it is not practical to employ MRS as a diagnostic tool for PD. DOI: http://dx.doi.org/10.3126/ajms.v4i3.8066 Asian Journal of Medical Sciences 4(2013) 76-85